Sweltsa yurok (Plecoptera: Chloroperlidae), a new stonefly from California, U.S.A. - Stark, Bill P. (Illiesia, 2007)
Sweltsa yurok, sp. n. is described from specimens collected in the Coast Rangeof northern California. The new species is compared to S. pisteri Baumann& Bottorff, and S. tamalpa (Ricker), closely related species found in the same region, and a provisional key to males of the Sweltsa tamalpa speciesgroup is presented.
Keywords: entomologija; Plecoptera; insekti; vrbnice; California; Kalifornija; United States of America; ZDA